2021
DOI: 10.1088/1748-9326/abef8c
|View full text |Cite|
|
Sign up to set email alerts
|

From lab-to-road: real-world fuel consumption and CO2 emissions of plug-in hybrid electric vehicles

Abstract: Plug-in hybrid electric vehicles (PHEVs) combine an electric motor with an internal combustion engine and can reduce greenhouse gas emissions from transport if mainly driven on electricity. The environmental benefit of PHEVs strongly depends on usage and charging behaviour. However, there is limited evidence on how much PHEVs actually drive on electricity and how much conventional fuel they use in real-world operation. Here, we provide the first systematic empirical analysis of real-world usage and fuel consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 13 publications
1
54
1
Order By: Relevance
“…The emissions-saving potential of PHEVs compared with conventional ICE vehicles is therefore highly dependent upon the share of kilometres driven in electric mode, also known as the utility factor. Recent analysis (Plötz et al, 2021) focused on cars, highlights that during real-world driving, the utility factors of passenger cars are consistently lower (approximately 50% on average) than reference values used for vehicle testing procedures (used to assign fuel economy ratings to new vehicles). This means that fuel economy and vehicle CO2 ratings given to vehicles overstate the environmental benefits of PHEVs -as shown in Figure 3 (left), which presents the sensitivity of vehicle lifecycle emissions of PHEVs with different utility factors.…”
Section: A Focus On Plug-in Hybrid Vehiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…The emissions-saving potential of PHEVs compared with conventional ICE vehicles is therefore highly dependent upon the share of kilometres driven in electric mode, also known as the utility factor. Recent analysis (Plötz et al, 2021) focused on cars, highlights that during real-world driving, the utility factors of passenger cars are consistently lower (approximately 50% on average) than reference values used for vehicle testing procedures (used to assign fuel economy ratings to new vehicles). This means that fuel economy and vehicle CO2 ratings given to vehicles overstate the environmental benefits of PHEVs -as shown in Figure 3 (left), which presents the sensitivity of vehicle lifecycle emissions of PHEVs with different utility factors.…”
Section: A Focus On Plug-in Hybrid Vehiclesmentioning
confidence: 99%
“…The real-world utility factor of PHEVs tends to be higher for vehicles with longer electric range and differs by country; for example, utility factors for plug-in hybrid cars have been found to be higher in Norway than in China (Plötz et al, 2021). Potential reasons include that fuel is relatively expensive compared with electricity in Norway and vehicles tend to have easier access to charging infrastructure -with charging occurring most frequently at home or at the workplace (IEA, 2018b).…”
Section: A Focus On Plug-in Hybrid Vehiclesmentioning
confidence: 99%
“…Unlike BEVs, the environmental gains derived from PHEVs depend on the distance driven while in electric mode. A study has reported that PHEV fuel consumption and tailpipe CO 2 emissions during real-world driving, on average, are approximately 2-4 times higher than type-approval values [12]. This is attributed to the small battery capacities, underpowered electric motors, and the absence of fast charging capabilities in some models, making it practically difficult for them to be driven properly on zero emission mode.…”
Section: Introductionmentioning
confidence: 99%
“…The automobile industry has presented the combination of a combustion engine with an electric engine (hence, plug‐in hybrid) as a meaningful development to meet the environmentally required need to reduce carbon dioxide emission, but still maintain the flexibility of modern mobility and avoid range anxiety. While this technical alliance may serve its purpose for specific situations, its value has been questioned for the general lack of efficiency improvement 1 …”
Section: Introductionmentioning
confidence: 99%